Differential contributions of brainstem structures to neurological soft signs in first- and multiple-episode schizophrenia spectrum disorders - Fritze, Stefan; Bertolino, Alina; Kubera, Katharina Maria; Topor, Cristina E.; Schmitgen, Mike; Wolf, Robert Christian; Hirjak, Dusan (Schizophrenia research, 2019)
Neurological soft signs (NSS) are frequently found in patients with schizophrenia spectrum disorders (SSD) at any stage of the disease. Brainstem structures are crucial for motor control, integration of sensory input and coordination of automatic motor actions. It is unclear whether disease duration has an impact on NSS/brainstem volume relationships. We tested the hypothesis that volumes of brainstem structures differ between first-episode psychosis (FEP) and multiple-episodes psychosis (MEP) patients with SSD, and that alterations of these structures are associated with NSS. T1-weighted structural MRI data at 3T were obtained from 92 right-handed SSD patients (27 FEP and 65 MEP). FreeSurfer vers. 6.0 was used for segmentation of brainstem structures including the medulla oblongata, pons, superior cerebellar pedunculus (SCP), and midbrain. Multiple regression analyses were used to describe the relationship between brainstem structures and distinct NSS subdomains. In FEP, pons volume had a significant effect on NSS total score (p=0.001, Bonferroni corr.). Further, medulla oblongata (p=0.001, Bonferroni corr.) and pons (p=0.001, Bonferroni corr.) volumes had a significant effect on NSS motor coordination score. In MEP, significant associations between brainstem structures and NSS levels were not found. The present data support the notion that brainstem structures play an important role in the expression of NSS in SSD individuals with FEP, in contrast to individuals with MEP. Our study also emphasizes the need of better characterizing episode-specific brainstem correlates of NSS in SSD.
Available online 7 June 2019
Gesehen am 11.05.2020